Complete response to anti-PD-L1 antibody in a metastatic bladder cancer associated with novel MSH4 mutation and microsatellite instability. Issue 1 (26th March 2020) - Yang, Yuanquan; Jain, Rohit K; Glenn, Sean T; Xu, Bo; Singh, Prashant K; Wei, Lei; Hu, Qiang; Long, Mark; Hutson, Nicholas; Wang, Jianming; Battaglia, Sebastiano; George, Saby
Abstract : Background: Microsatellite instability (MSI) occurs in 3% of urothelial carcinomas as a result of germline or somatic loss of function mutation in mismatch repair (MMR) proteins.1 Although MSH4 is a member of the DNA MMR mutS family, the association of MSH4 mutation with MSI has not been described. We report a complete responder to PD-L1 blockade who had MSH4 mutated metastatic bladder cancer with mixed histology and MSI. The genomics of urothelial, plasmacytoid and squamous histology was characterized individually through microdissection. Case presentation: An 81-year-old man was diagnosed with metastatic urothelial carcinoma 8 months after a cystectomy for muscle invasive bladder cancer. His disease was primary refractory to first-line platinum-based chemotherapy but attained complete response to second-line atezolizumab. PCR-based assay revealed MSI high. The tumor mutational burden was elevated to 36.7 mut/Mb. However, immunohistochemistry of MLH1, MSH2, MSH6 and PMS2 was intact. Whole exome sequencing confirmed that the above mentioned four classic MMR genes were wild type but revealed a deleterious MSH4 L359I mutation with variant allele fraction of 30% and Polyphen2 score of 0.873. The association of MSH4 alterations and MSI-H was independently verified in two publicly available MSI-H colorectal cancer datasets. Conclusions: The novel MSH4 L359I mutation is associated with MSI and high mutational burden leading to remarkable response to PD-L1 blockade. More studies are warranted to establish the causality relationship between MSH4 and MSI.